Dugaan Praktik Pelanggaran Hukum Insider Trading Yang Dilakukan Terhadap Investor Pasar Modal Indonesia (Studi Kasus PT. Jouska Finansial Indonesia) - Ragil Ibnu Fatah Rialdy; Inda Rahadiyan (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study analyzed the alleged insider trading practices carried out by PT Jouska Finansial Indonesia against Indonesian capital market investors. Based on the formulation of the problem, (1) What are the indications of alleged insider trading practices carried out by PT Jouska Finansial Indonesia. (2) How is the form of legal protection for investors on the occurrence of alleged insider trading practices carried out by PT Jouska Finansial Indonesia. This research uses normative legal research methods with a statutory and case approach. The legal materials used are primary and secondary, and are analyzed qualitatively. The results of this study show, (1) PT Jouska Finansial Indonesia is included in the existing elements of insider trading, namely the existence of insiders, material information that is not yet available to the public, and making transactions due to material information. (2) The legal protection carried out is the imposition of a verdict with number 220/Pid.Sus/2022/2022/PN Jkt.Pst which was strengthened at the High Court level with number 261/Pid.Sus/2022/PT. DKI imposing each defendant with imprisonment for 6 years and 6 months and a fine of Rp 2,000,000,000, - (two billion rupiah).